2019
DOI: 10.1007/s11666-019-00904-x
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Suspension Thermal Spray Patented Technology Evolution

Abstract: Since the introduction of suspension thermal spray (STS) in 1997, the rapid evolution of this technology has resulted in a critical number of inventions justifying a comprehensive review. Today STS is one of the most important research and development topics in thermal spray. Due to the efforts of different industries, universities, and governmental institutions, STS has reached a certain maturity for implementation in different applications. STS includes any thermal spray process that is based on injection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Thermal spraying is a widely employed technique for depositing HA and HA composite materials. 27,[63][64][65][66][67][68] Dental and orthopedic prosthetic devices, including hip and knee implants and bone fracture fixing devices such as bone plates, screws, and pins, are modified with HA coatings. 69 Currently, FDA approved the plasma-spray technique to deposit HA coatings on the metal substrate.…”
Section: Bone and Surface Modifications Of Biomaterialsmentioning
confidence: 99%
“…Thermal spraying is a widely employed technique for depositing HA and HA composite materials. 27,[63][64][65][66][67][68] Dental and orthopedic prosthetic devices, including hip and knee implants and bone fracture fixing devices such as bone plates, screws, and pins, are modified with HA coatings. 69 Currently, FDA approved the plasma-spray technique to deposit HA coatings on the metal substrate.…”
Section: Bone and Surface Modifications Of Biomaterialsmentioning
confidence: 99%
“…[103] This can then be followed by managing the process parameters of thermal spray to melt (or partially melt) the powder particles and preserve its fine-grained structures or use liquid feedstock (suspension, solution) to change the interaction between hot gases and feedstock in the way to enable obtaining finely grained coatings. [6,24,103,[170][171][172] Considering some examples where suspension-based plasma spray coating has been developed by Vaßen et al (2009), [93] Mauer, Guignard and Vaßen (2013), [111] Robinson et al ( 2015), [106] and Khatibnezhad et al (2021), [105] for photocatalytic (absorption) applications, future work may be promising in the current context, where suspension or solution spraying (SPS, SPPS) can allow convenient deposition of range of coatings to yield desirable EM wave propagation properties.…”
Section: Application Of Suspension Solution or Hybrid Thermally Spray...mentioning
confidence: 99%
“…Recent trends have been to produce thermally sprayed ceramic coatings with nanostructures or refined microstructures and precision-engineered surface textures. [5,6] Thermal spray grade powder particle shape, geometry, size, orientation, and arrangement during thermal spraying of a chosen material can affect the EM waves in an unconventional manner, thereby creating material (surface) properties which are not achievable using conventional processes.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical [11,12] and experimental studies [13,14] have demonstrated that the solid particle interaction with plasma includes a large number of different physical phenomena; therefore, its complete description is practically impossible. The physical and mathematical model of melting of a quartz particle in low-temperature plasma was developed in [15].…”
Section: Introductionmentioning
confidence: 99%